THE IMPACT OF CAREER DEVELOPMENT, ORGANIZATIONAL COMMITMENT, AND JOB INSECURITY ON TURNOVER INTENTION - Widi Wahyudi; Burhanuddin Qodri (STABILITY : Journal of Management and Business, 2025)
The purpose of this research is to identify how work insecurity, lack of career growth opportunities, and lack of organizational commitment at PT Sanita Sukses Mandiri Jakarta contribute to employee turnover intentions. This study is a quantitative study, and the population consists of actual working people. Saturated sampling was employed for this investigation, and 75 people ended up participating. A questionnaire was used to gather information. IBM's SPSS version 25 was utilized for the study's data analysis. This research found that there was an association between job insecurity and turnover intent, but that career development and organizational commitment also affected intentions to leave.